Dis-adoption of household biogas technologies in Central Uganda - Lwiza, F.; Mugisha, J.; Walekhwa, P.N.; Smith, J.; Balana, Bedru (Elsevier, 2017)
The study analyses dis-adoption of biogas technologies in Central Uganda. Biogas technology makes use of livestock waste, crop material and food waste to produce a flammable gas that can be used for cooking and lighting. Use of biogas technology has multiple benefits for the households since it reduces the need for fuelwood for cooking and also produces bio-slurry which is a valuable fertilizer. Despite efforts by Government and Non-Governmental Organizations to promote the biogas technology, the rate of its adoption of biogas technology was found to be low, estimated at 25.8% of its potential. A review of literature showed that the households that dis-adopted biogas technology, did so within a period of 4 years after its installation, yet the lifespan of using it is estimated at 25 years. There was need to examine the factors contributing to dis-adoption. Using cross sectional data collected from Luwero and Mpigi districts found in Central Uganda, a probit model was estimated. The findings showed that an increase in the family size, the number of cattle, number of pigs and the age of the household head reduced the likelihood of biogas technology dis-adoption. Other factors that contributed to dis-adoption included the failure to sustain cattle and pig production that are necessary for feedstock supply, reduced availability of family labor the and inability of the households to repair biogas digesters after malfunctioning. Based on the findings, it was concluded that long term use of biogas technology required improved management practices on the farm so as to sustain livestock production. It is also recommended that quality standards and socio-cultural factors be considered in the design of biogas digesters and end use devices.